Clinical Evaluation of Xylazine-Zoletil Anesthesia in Equine under Field Conditions - Babbar, Nikhil; Khandekar, Gajendra S.; Tripathi, Santosh D.; Saini, Dishant; Gaikwad, Shahir V.; Chauhan, Shalaka A. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was conducted on eighteen horses divided into three groups, consisting of six horses in each irrespective of their size, breed and body weight. Horses from all groups were pre-anaesthetized with xylazine (1.1 mg/kg b.wt.) intravenously and anesthetized after 5 min with doses of zoletil (Tiletamine and zolazepam) @ 0.5 mg/kg, 0.8 mg/kg and 1.1 mg/kg BW in groups I, II and III, respectively. Evaluation of different parameters like time of induction of anaesthesia, quality of induction, duration of anaesthesia, degree of muscle relaxation, time and quality of recovery were evaluated and compared between the groups. Different haematological, biochemical and clinical parameters were studied before administration of pre-anaesthetic, during anaesthesia and after complete recovery. There was no significant difference noted for clinical, haematological, biochemical and anaesthetic parameters between the three groups. Quality of induction and anaesthesia was better in group II and group III than group I. Time required attaining sternal recumbency, standing and completing recovery were significantly longer in group III than group I and group II. Overall quality of recovery was better in group I and group II than group III.  On the basis of this study, we can say zoletil at a dose rate of 0.8 mg per kg body weight provide better quality of field anaesthesia associated with smooth recovery for short term surgical procedures like gelding.
Keywords: Anaesthesia; Equine; Gelding; Tiletamine; Zolazepam